Human Skeleton: Assistance in making learning media from paper waste in the Movement System material - Mia Nurkanti; Rani Darmayanti; Akhsanul In'am (Jurnal Dedikasi, 2023)
Blue garbage cans can also sort paper waste. Sorting paper trash aids recycling. Poor waste processing can harm the environment by releasing high organic content, chlorinated organic partitions, carcinogenic substances, and hormone-interfering substances that disrupt the aquatic ecosystem and reduce fish, shellfish, and other species. Methane causes fire. Clean water sources are shrinking. It's important to recycle plastic trash, including paper waste as a learning medium. Helping MTs Pasuruan make learning media from paper waste utilizing movement system material using plastic waste. This action aims to: Students may learn about the environment and be more motivated to study by producing learning media from paper trash. Students have made paper waste learning material for classroom and outside-class usage. The process involves planning, execution, and assessment. Movement system material was used for paper-based media since human skeletal learning media is not yet accessible. Students that engaged in this program were more environmentally conscious, particularly regarding paper waste. Additionally, MTs have human movement tool learning media.